2012
DOI: 10.1080/1745039x.2012.676812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary benzoic acid and sodium-benzoate on performance, nitrogen and mineral balance and hippuric acid excretion of piglets

Abstract: The objective of this study was to compare the effects of sodium-benzoate (NaB) with those of benzoic acid (BAc) on growth performance of piglets as well as nutrient digestibility, nitrogen and mineral balance, urinary pH, and the urinary excretion of BAc and hippuric acid (HAc). The study was conducted with 120 weaning piglets (6.5 kg body weight), divided in four groups (15 replicates of two piglets each), which received (1) a basal diet (Control), or the basal diet supplemented with (2) 4 g NaB per kg (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Dietary proper ( ≤ 0.5%) benzoic acid supplementation can improve the growth performance of weaned pigs (Halas et al, 2009;Halas et al, 2010;Gräber et al, 2012;Diao et al, 2015;Diao et al, 2016). And the dosage of benzoic acid can be increased to 1.0% or 2.0% in the diets of growing pigs or lactating sows (Buhler et al, 2006;Sauer et al, 2009;Kluge et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dietary proper ( ≤ 0.5%) benzoic acid supplementation can improve the growth performance of weaned pigs (Halas et al, 2009;Halas et al, 2010;Gräber et al, 2012;Diao et al, 2015;Diao et al, 2016). And the dosage of benzoic acid can be increased to 1.0% or 2.0% in the diets of growing pigs or lactating sows (Buhler et al, 2006;Sauer et al, 2009;Kluge et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have indicated that the effect of benzoic acid used in the farming field are closely related to its dosage (Kluge et al, 2010;Papadomichelakis et al, 2011;Gräber et al, 2012). Dietary proper ( ≤ 0.5%) benzoic acid supplementation can improve the growth performance of weaned pigs (Halas et al, 2009;Halas et al, 2010;Gräber et al, 2012;Diao et al, 2015;Diao et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…coli, a major etiological agent of postweaning colibacillosis (Fairbrother et al 2005). In their undissociated form, organic acids passively diffuse through the bacterial cell wall and interfere with the fine-tuned pH balance in the cytoplasm, which upsets the energy balance and disrupts biochemical processes leading to cell death (Kluge et al 2006;Gräber et al 2012). Organic acids have also been reported to suppress bacterial cellular enzymes and nutrient transport system under in vitro tests (Knarreborg et al 2002;Friedman et al 2003).…”
Section: Itemsmentioning
confidence: 99%
“…Benzoic acid (BA) is a phenyl formic acid which belongs to the group of weak organic acids. Benzoic acid has been shown to be beneficial on growth performance, nutrients digestibility, and indices of gut health in piglets (Kluge et al 2006;Guggenbuhl et al 2007;Torrallardona et al 2007;Gräber et al 2012;Diao et al 2016). In vitro studies have shown that, of several organic acids tested, BA had the strongest antimicrobial effect on Escherichia coli and salmonella, among other pathogens (Knarreborg et al 2002;Friedman et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The dietary inclusion of organic acids usually improves growth performance. Although benzoic acid does not change the pH of the stomach, duodenum or jejunum contents of pigs (Kluge, Broz, & Eder, ; Maribo, Olsen, Mishler, Jensen, & Miquel, ), it has shown positive effects on piglet performance (Alvarado, López, Varela, Landín, & Ibargüengoytia, ; Diao et al., , ; Gheler et al., ; Gräber, Kluge, Hirche, Broz, & Stangl, ; Halas et al., ; Papatsiros et al., ). However, the action of benzoic acid is not fully understood, especially in challenge situations, and previous studies have not reported on the residual effects of benzoic acid supplementation in the nursery phase on the performance in the finishing phase.…”
Section: Introductionmentioning
confidence: 99%